2001
DOI: 10.1097/00005373-200111000-00017
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Curcumin against Oxidative Damage on Skin Cells In Vitro: Its Implication for Wound Healing

Abstract: The findings indicate that curcumin indeed possessed powerful inhibition against hydrogen peroxide damage in human keratinocytes and fibroblasts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
115
0
9

Year Published

2003
2003
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 213 publications
(128 citation statements)
references
References 23 publications
4
115
0
9
Order By: Relevance
“…Certain reports have shown that curcumin can quench singlet oxygen and can inhibit the production of H 2 O 2 in an aqueous environment (Phan et al, 2001;Das and Das, 2002). The ameliorated process of such antioxidant and free radical scavenging properties of cAuNps over free curcumin can be due to their interaction patterns of phenolic-OH and by abstraction of H atom from C12 methylene group of curcumin (Balasubramanyam et al, 2003;Hatcher et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Certain reports have shown that curcumin can quench singlet oxygen and can inhibit the production of H 2 O 2 in an aqueous environment (Phan et al, 2001;Das and Das, 2002). The ameliorated process of such antioxidant and free radical scavenging properties of cAuNps over free curcumin can be due to their interaction patterns of phenolic-OH and by abstraction of H atom from C12 methylene group of curcumin (Balasubramanyam et al, 2003;Hatcher et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…It exhibits strong antioxidant, anti-inflammatory, and antimicrobial properties that make it a great candidate for wound healing applications. [8][9][10][11] Besides these properties, it is also attractive for its availability, stability, low cost, and safety, which was demonstrated in numerous clinical trials. The effect of curcumin depends mainly on the dose to which cells are exposed.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, it also increases the synthesis of hexosamine, collagen, nitrite, DNA, and histologic determination of wound biopsy specimens that improves the collagen deposition and also enhances in fibroblast ( Jagetia & Rajanikant 2005). Phan et al (2001) determined that the oral dose of curcumin (2.5 µg/ml) showed the significant protective effect against H 2 O 2 to human dermal fibroblasts. Lee (2006) reported that curcumin has an inhibitory effect on platelet aggregation induced by collagen and arachidonic acid.…”
Section: Curcumin Enhanced Wound Healingmentioning
confidence: 97%